TEOLOGI LINGKUNGAN; Studi Fenomenologi Gerakan Environmentalisme Komunitas Air Kita Mojoagung - Amilatul Khasanah; Naibin Naibin (Jurnal Sosiologi Agama, 2021)
In modern era, environmental issues placed with religion are being seriously discussed by academics and some elements of society who are concerned about the problem of ecological crisis, as a result of threat life. The environmentalism movement is to instill consciousness in their reactions to nature. This consciousness of being environmentally friendly is carried out by the Air Kita Mojoagung Community which focuses on the movement of utilizing rainwater. This research aims to describe the religious motivational experience Air Kita Community through the rainwater conservation movement. The study was conducted using a qualitative method with a phenomenological approach that is oriented to data from in-depth interviews, field observations, documentation and literature studies. Classified data presented descriptively analysis. Results the research indicate that although it is seen in the meaning of water capitalization, the factor of religious doctrine is strong in motivating environmental movement. This can be seen in the approach used namely rainwater sholawat festival with the strengthening of the Javanese art tradition of wayang beber and the Javanese Islamic art of gambus misri 9 stars, nadah udan in the realm of praxis which means that rainwater is a blessing and a gift, God’s presence that should not be wasted.